2023
DOI: 10.1192/bjo.2022.643
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making and best practice when nasogastric tube feeding under restraint: multi-informant qualitative study

Abstract: Background Clinicians working in mental health in-patient settings may have to use nasogastric tube feeding under physical restraint to reverse the life-threatening consequences of malnutrition when this is driven by a psychiatric condition such as a restrictive eating disorder. Aims To understand the decision-making process when nasogastric tube feeding under restraint is initiated in mental health in-patient settings. Method People with lived experience of nasogastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…To our knowledge, this is the first national survey and case series of CYP receiving NGT feeding under restraint in English paediatric wards with the only similar previous research undertaken in mental health inpatient units in England 8 12 13. We found that around a third of paediatric units had provided NGT under restraint in the previous year.…”
Section: Discussionmentioning
confidence: 58%
“…To our knowledge, this is the first national survey and case series of CYP receiving NGT feeding under restraint in English paediatric wards with the only similar previous research undertaken in mental health inpatient units in England 8 12 13. We found that around a third of paediatric units had provided NGT under restraint in the previous year.…”
Section: Discussionmentioning
confidence: 58%
“…Research suggests that the best practice is advance care planning between patients, carers and the clinical team where there is a joint discussion and agreement regarding and potential use of restrictive practices and the conditions under which they might occur. 6 This should help individuals have a sense of ownership of the decision-making and understand that the clinicians are working with them from the start. This could become critical to success and collaboration if patients subsequently lose weight to the point of medical instability and clinicians need to consider overriding their wishes.…”
Section: Discussionmentioning
confidence: 99%
“…This could become critical to success and collaboration if patients subsequently lose weight to the point of medical instability and clinicians need to consider overriding their wishes. 21 , 24 , 25 Advance care planning can promote patient participation and prevent loss of agency when clinicians need to employ restrictive measures and help shift the narrative from ‘They are doing this to me, I didn't know this would happen, they just suddenly decided they would,’ to ‘This is my care plan, I did know this might happen and furthermore I do know why even if I can't agree.’ 6 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations